Analisis Tindak Tutur Direktif pada Daftar Putar Video Pembelajaran Bahasa Indonesia Quipper Video - Jaroatin Nabila; Maulida Zahra Qutratu'ain; Chaerunnissa Chaerunnissa; Muhamad Diky Yulianto; Asep Purwo Yudi Utomo (Universitas Sebelas Maret, 2023)
The study of directive speech acts underlies this study. Speech acts used to direct other people or state what the speaker wants are known as directive speech acts. Directive speech acts serve a number of functions, including commands, requests, invitations, advice, criticism, and prohibitions, etc. The objective of this study was to discover and describe numerous types of directive speech acts in Quipper Vidio Indonesian Language Learning videos based on the functions of commands, requests, invitations, advice, criticism, and prohibitions, etc. This study was designed with a qualitative descriptive method which shows where there is evidence of directive speech acts and explaining them based on existing facts in line with the explanation to enable to produce a presentation as it is. The study data collected was obtained from five video sources on YouTube. Based on the results of this study, there are 25 command functions, 6 request functions, 36 invitation functions, 15 advise functions, 0 criticism functions, and 1 prohibition function. The objectives of this study are to improve the theory of language development by studying the form of directive acts in the learning objects to be studied. It is expected that the study will expand readers' perspectives on directive speech acts as well as classifying the functions of directive speech acts in the Quipper Vidio Indonesian Language Learning playlist.